Βιβλιοκρισία:M. HINTERBERGER (ed.), The Language of Byzantine Learned Literature [BYZANTIOς. Studies in Byzantine History and Civilization 9], Turnhout 2014, σελ.VI+228. - ΛΑΜΠΑΚΗΣ Στυλιανός (Byzantina Symmeikta, 2016)
Βιβλιοκρισία:M. HINTERBERGER(ed.), The Language of Byzantine Learned Literature [BYZANTIOς. Studies in Byzantine History and Civilization 9], Turnhout 2014, σελ.VI+228.